Digitalisasi Pemasaran Ikan Asin Pulau Pasaran Menggunakan Aplikasi Google Playstore Berbasis Android - Niken Kusumawardani; Dewi Sukmasari; Agus Zahron (Universitas Teknokrat Indonesia, 2025)
This community service activity aims to enhance the knowledge and skills of micro, small, and medium enterprise (MSME) actors in Pulau Pasaran Village, Sukaraja Subdistrict, Bandar Lampung City, in marketing their salted fish products through digitalization strategies utilizing Android-based applications. The methods employed in this activity included a combination of training, mentoring, and socialization. The training provided MSME actors with the skills to use Android-based applications for marketing salted fish products. Mentoring was conducted to assist MSME actors in implementing the knowledge gained during the training. Socialization aimed to inform the community about the benefits of using Android-based applications to purchase salted fish products. The results of this activity successfully improved the understanding of utilizing digital marketing applications among salted fish producers in Pulau Pasaran. Furthermore, practical assistance was provided to ensure effective application use. This activity led to a behavioral shift among salted fish producers in Pulau Pasaran, transitioning from conventional marketing methods to digitalization strategies.